Strategi Peningkatan Mutu Perguruan Tinggi - Qoyyimun Nafal; Sokip Sokip; Asrop Syafi’i (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The strategy to improve the quality of higher education cannot be separated from a development system that is planned, directed and organized in running the organization, productive efforts and breakthroughs really need to be carried out and developed because higher education is a forum for producing intellectual generations as well as producing generations who have moral character. The strategy for improving the quality of higher education does not only start from building adequate infrastructure but also must pay attention to increasing the competency of human resources (HR), so that they have good quality competence, both at the national and international level because quality universities are capable of responding to the challenges, needs and desires of society in line with the progress and development of science that continues to advance.